Development of a broadband Mueller matrix ellipsometer as a powerful tool for nanostructure metrology - Liu, Shiyuan; Chen, Xiuguo; Zhang, Chuanwei (Thin solid films, 2015)
Ellipsometric scatterometry has gained wide industrial applications in semiconductor manufacturing after ten years of development. Among the various types of ellipsometers, Mueller matrix ellipsometer (MME) can provide all 16 elements of the 4 by 4 Mueller matrix, and consequently, MME-based scatterometry can acquire much more useful information about the sample and thereby can achieve better measurement sensitivity and accuracy. In this paper, the basic principles and instrumentation of MME are presented, and the data analysis in MME-based nanostructure metrology is revisited from the viewpoint of computational metrology. It is pointed out that MME-based nanometrology is essentially a computational metrology technique by modeling a complicated forward process followed by solving a nonlinear inverse problem. Several case studies are finally provided to demonstrate the potential of MME in nanostructure metrology. •Principles of Mueller matrix ellipsometry (MME) based scatterometry are presented.•We developed a broadband dual rotating-compensator Mueller matrix ellipsometer.•The data analysis is revisited from the viewpoint of computational metrology.•Potential of MME in nanostructure metrology is demonstrated using case studies.